2021
DOI: 10.7150/jca.60543
|View full text |Cite
|
Sign up to set email alerts
|

FHL1 Inhibits the Progression of Colorectal Cancer by Regulating the Wnt/β-Catenin Signaling Pathway

Abstract: Purpose: This study aims to explore the FHL1 expression level in colorectal cancer (CRC) patients, analyze its association with patient survival and investigate the role of FHL1 in CRC. Methods: We used secondary sequencing to profile mRNA expression in CRC tissue and corresponding adjacent normal tissue from four CRC patients. We focus on FHL1 and analyzed the association between its expression level and clinical indicators. Furthermore, we explored the functional role of FH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…Upregulation of FHL1 has been shown to inhibit cell invasion by increasing RhoGDIß expression in lung cancer . Wnt/β-catenin signaling is a crucial pathway in EMT regulation, and FHL1 has been reported to negatively modulate the Wnt/β-catenin signaling pathway in colorectal cancer . Our study observed that tabersonine upregulated FHL1 protein levels in a dose-dependent manner.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Upregulation of FHL1 has been shown to inhibit cell invasion by increasing RhoGDIß expression in lung cancer . Wnt/β-catenin signaling is a crucial pathway in EMT regulation, and FHL1 has been reported to negatively modulate the Wnt/β-catenin signaling pathway in colorectal cancer . Our study observed that tabersonine upregulated FHL1 protein levels in a dose-dependent manner.…”
Section: Resultssupporting
confidence: 54%
“…45 Wnt/β-catenin signaling is a crucial pathway in EMT regulation, and FHL1 has been reported to negatively modulate the Wnt/β-catenin signaling pathway in colorectal cancer. 46 Our study observed that tabersonine upregulated FHL1 protein levels in a dose-dependent manner. Furthermore, FHL1 knockdown restored the invasive and migratory abilities of the OVC cells after tabersonine treatment, accompanied by the reestablishment of E-cadherin, Ncadherin, and vimentin expression.…”
Section: Identification Of Tabersonine As a Potent Inhibitor Increasi...mentioning
confidence: 48%
“…Current studies have shown that recombinant Helicobacter Pylori aspartate ammonialyase (ASPA) is an effective predictor of prognosis in colorectal cancer patients 52 . Four-and-a-half LIM domains protein (FHL1) has a diagnostic value in microscopic papillary thyroid carcinoma 53 , and it has been reported that FHL1 acts as an inhibitor in colorectal cancer cells [54][55][56] . Receptor activity-modifying protein 3 (RAMP3) is an accessory molecule that forms complexes with and regulates the function of specific G protein-coupled receptors (GPCRs).…”
Section: Discussionmentioning
confidence: 99%
“…To understand if these gene expression changes are responsible for driving CPSF3 knockdown-mediated phenotypes, we determined the requirement for FHL1 expression in mediating cell proliferation. FHL1 possesses tumor suppressing activity in different cancer types but has not been investigated in the context of PDAC (2932). We find that silencing of FHL1 , in the context of CPSF3 knockdown, sufficiently rescues the defect in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, this list included multiple downregulated oncogenes, including SMAD Family Member 6 (SMAD6) and Mitogen-Activated Protein Kinase Kinase 6 We next sought to determine if any of the APA-regulated oncogenes or tumor suppressors were directly responsible for CPSF3 knockdown-mediated attenuation of cell proliferation. We focused on FHL1, as it has been reported to possess tumor suppressor activity in non-PDAC cancers (29)(30)(31)(32), but has no known roles in PDAC biology. FHL1 interacts with transcription factors and signaling proteins, thus modulating gene transcription and signaling pathways (29,33).…”
Section: Cpsf3 Knockdown Dysregulates Global Gene Expression In Pdac ...mentioning
confidence: 99%